Зберігання зелені коріандру (Coriandrum sativum L.) в живильному середовищі - Прісс, Олеся Петрівна; Присс, Олеся Петровна; Priss, Olesia; Сухаренко, Олена Іванівна; Сухаренко, Елена Ивановна; Sukharenko, Olena; Коляденко, Вікторія Вікторівна; Коляденко, Виктория Викторовна; Koliadenko, Viktoriia; Нестеров, Ю. Ю. (My University, 2019)
UK: Зелень коріандру (Coriandrum sativum L.) одна з найбільш широко використовуваних свіжих трав у світі. Свіжозрізану зелень важко зберігати без втрая якісних характеристик. При дотримання температуро - вологістних режимів, втрата аромату, високі природні втрати маси зелені та її пожовтіння призводять до скорочення терміну зберігання. Для подовження термінів зберігання і стабілізації вмісту біологічно активних речовин запропонована технологія зберігання зелені коріандру в живильному середовищі на основі гідрогелю та хлорофіліпту. Встановлено, що зберігання зелені коріандру у живильному середовищі з гідрогелем та хлорофіліптом забезпечує подовження терміну зберігання, скорочує природні втрати маси, стабілізує вміст пігментів. RU: Зелень кориандра (Coriandrum sativum L.) одна из наиболее широко используемых свежих трав в мире. Свежесрезанные травы трудно хранить без потери качественных характеристик. При соблюдении температурно - влажностных режимов, потеря аромата, высокие естественные потери массы и пожелтение зелени приводят к сокращению срока хранения. Для удлинения сроков хранения и стабилизации содержания биологически активных веществ предложена технология хранения зелени кориандра в питательной среде на основе гидрогеля и хлорофилипта. Установлено, что хранение зелени кориандра в питательной среде с гидрогелем и хлорофилиптом обеспечивает продление срока хранения, сокращает естественные потери массы, стабилизирует содержание пигментов. EN: Cilantro (Coriandrum sativum L.) is one of the most widely used fresh herbs in the world. Freshly cut greenery is difficult to store without losing its quality. In case of maintaining temperature and humidity regimes shelf life time decreases due to high natural loss of green mass, its yellowing and the loss of flavor. The method of cilantro storage in the hydrogel-chlorophyllipt-based nutrient medium was suggested in order to prolong spinach shelf life and to stabilize biologically active substances. Fresh leaves of cilantro were collected in 50g bundles, tied with an elastic band, cooled to a temperature of about 5 °C and transported to the lab within 2 hours after harvesting. In the laboratory stems of greenery were put in polyethylene bags, which were pre-filled with nutrient medium 1% hydrogel (variant 1) or same 1% hydrogel with 0.25% chlorophyllipt acting as antioxidant (variant 2). The control variant was left without the nutrient environment. Bags with bundles of greenery were packed into boxes and stored under the ± 0, 5 ° C and relative humidity of air 95 ± 3%. Basing on the conducted research it was established that usage of hydrogel-based nutrient medium allows to prolong the shelf life of cilantro 3.0... 3.5 fold (depending on the variant) comparing with the control group. The usage of hydrogel-based nutrient medium reduces natural loss of weight 2.2... 2.5 fold. After the 3.5 fold-prolonged cilantro storage period in the hydrogel-chlorophyllipt-based nutrient medium greenery had the same hedonic assessment as the control. Application of the nutrient medium slowers the chlorophyll and carotenoids degradation during the cilantro shelf life. In greenery stored in the chlorophyllipt-containing nutrient medium the level of chlorophylls concentration is higher by 24.6% compared to control, and the concentration of carotenoids by 49.7%.
Хранение зелени кориандра (Coriandrum sativum L.) в питательной среде
Cilantro (Coriandrum sativum L.) storage n nutrient medium
Keywords: зелень коріандру; зберігання; живильне середовище; гідрогель; природні втрати маси; пігменти; зелень кориандра; хранение; питательная среда; гидрогель; естественная убыль массы; пигменты; cilantro; storage; nutrient medium; hidrogel; pigments; natural loss of mass